2020
DOI: 10.1038/s41415-020-1370-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of polishing systems on surface roughness and morphology of dental composite resin

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
7
20
0
Order By: Relevance
“…The finding that polishing with the Enhance PoGo system resulted in similar smooth surfaces of both composites as the Mylar formed surfaces is similar to the findings of Ergücü and Türkün [24], who concluded that Mylar strip-and PoGo finished Filtek Supreme XT surfaces were equally smooth. The mean surface roughness values of Sof-Lex polishers of both composites with Mylar formed surfaces in this study is comparable to another investigation by Wheeler et al [23] with similar surface examination methodology, which reported mean surface roughness values of 0.35 μm (SD 0.13), when applied to a submicron hybrid composite resin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that polishing with the Enhance PoGo system resulted in similar smooth surfaces of both composites as the Mylar formed surfaces is similar to the findings of Ergücü and Türkün [24], who concluded that Mylar strip-and PoGo finished Filtek Supreme XT surfaces were equally smooth. The mean surface roughness values of Sof-Lex polishers of both composites with Mylar formed surfaces in this study is comparable to another investigation by Wheeler et al [23] with similar surface examination methodology, which reported mean surface roughness values of 0.35 μm (SD 0.13), when applied to a submicron hybrid composite resin.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that microhybrid and nanofilled composites present low surface roughness immediately following polishing [19][20][21][22][23]. Based on this, clinicians may assume that these types of composites are the most adequate and aesthetic for the placement of state-of-the-art composite restorations.…”
Section: Discussionmentioning
confidence: 99%
“…While, regardless of the Reuse/Sterilization Cycle, the OptraPol Group showed the least statistically significant R a followed by the Dimanto Group, then the ProGloss Group. These variations in roughness average results between the different polishing systems in spite of being part of the same multi-use single-step polishers' category conforms with Wheeler et al 26 results on 2020 where the effects of five different two-step diamond impregnated polishing systems on the surface roughness and morphology of composite resin material was evaluated as they concluded their research that "Similarly designed polishing systems do not produce comparable surface roughness levels." The R a variations may be caused by the unequal distribution of abrasives in the delivery medium 7 , or the difference in abrasive diamond particles size 27 a factor that was found to affect the polishing system efficiency by Bashetty et al 7 where the fine diamond particles tips gave a much less roughness averages of the composite surface than the larger sized aluminum oxide particles polishing disks.…”
Section: Discussionsupporting
confidence: 79%
“…Another important consideration for polishing composite resins is the standardization of the force applied to the surface during polishing. In the present study, a light force was applied by a single operator for 45 s to minimize variations in the magnitude and duration of applied force (Wheeler, Deb, & Millar, 2020).…”
Section: Discussionmentioning
confidence: 99%